A clinical case of concurrent mycoplasma pneumonia and dengue hemorrhagic fever in a tourist from Thailand - N. A. Rozanova; M. A. Sayfullin; N. N. Zvereva; V. E. Larichev; Ya. E. Grigorieva; A. M. Butenko (Туберкулез и болезни лёгких)
The article describes a clinical case of concurrent infectious diseases - dengue hemorrhagic fever and mycoplasma pneumonia in a patient who came back from the area endemic for dengue fever. Further, the patient was diagnosed with clostridial colitis which was the complication. Clinical, laboratory, and radiological parameters used in the diagnosis of diseases were evaluated.